Microbe infection responsive metal-polyphenol / cinnamaldehyde nanocapsule, preparation method and application
Patent Information
- Application Number
- CN202611375825.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-09
AI Technical Summary
生物膜通过胞外聚合物(EPS)构建保护屏障,显著提升细菌对干燥、消毒剂及抗菌剂的耐受性(可达浮游菌的10-1000倍),使得常规杀菌措施难以彻底清除,极易造成复发污染,缩短货架期并增加食品安全隐患
1、本发明制备的微生物侵染响应型金属-多酚/肉桂醛纳米胶囊,利用致病菌(如金黄色葡萄球菌)分泌透明质酸酶的特性,HA外壳在酶作用下特异性降解,暴露内核并触发肉桂醛和镓离子的快速释放;在无酶无菌的环境下,HA外壳保持完整,有效防止肉桂醛挥发和氧化,降低非特异性消耗。
Smart Images

Figure CN122874435A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of antibacterial materials technology, specifically relating to microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules, their preparation method, and applications. Background Technology
[0002] Foodborne pathogens and spoilage bacteria contamination are significant sources of risk in the food safety field. Pathogenic bacteria, such as Staphylococcus aureus, Listeria monocytogenes, and Escherichia coli, can rapidly multiply on the surface of high-protein, high-moisture foods like meat products, leading to health hazards such as diarrhea, fever, and sepsis, and potentially triggering outbreaks of foodborne illnesses. Simultaneously, food is susceptible to cross-contamination during processing, transportation, and storage. Microorganisms adhere to food surfaces or processing equipment, further forming dense biofilms. These biofilms, through extracellular polymeric substances (EPS), construct a protective barrier, significantly increasing bacterial tolerance to desiccants, disinfectants, and antimicrobial agents (up to 10-1000 times that of airborne bacteria). This makes them difficult to completely eliminate with conventional sterilization measures, easily leading to re-contamination, shortening shelf life, and increasing food safety risks.
[0003] To inhibit microbial growth, various antimicrobial strategies have been developed in the food and related materials field, including: (1) chemical preservatives (such as organic acids, nitrites, etc.), which are characterized by low cost and easy operation, but may have problems such as flavor impact and limited applicability; (2) antibiotics or small molecule bactericides are widely used in non-food scenarios, but drug resistance is a prominent problem, and their use in the food field is strictly limited; (4) metal ions / metal nanomaterials (such as silver, zinc, copper, etc.) have strong antimicrobial activity, but may face problems such as potential biosafety concerns caused by non-specific release, insufficient selectivity for target bacteria, and limited penetration in biofilm environments; (5) antimicrobial coatings and packaging active materials can achieve sustained release and surface antimicrobial activity, but generally have problems such as release behavior being difficult to respond synchronously with the risk of pathogenic bacteria, and release under low bacterial load or aseptic conditions, resulting in wasted activity.
[0004] Cinnamaldehyde, a generally recognized safe (GRAS) natural plant essential oil, possesses broad-spectrum and highly effective antibacterial activity. However, its poor water solubility, volatility, easy oxidation, and pungent odor limit its direct application in food antibacterial preservation. Although existing microencapsulation technology has addressed the stability issue to some extent, most capsules have a single release mechanism (such as simple diffusion release) and lack the ability to intelligently respond to the bacterial microenvironment.
[0005] Therefore, the development of a microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsule, its preparation method, and its application are crucial for achieving on-demand release of active ingredients and efficient removal of pathogens and biofilms. Summary of the Invention
[0006] The purpose of this invention is to overcome the defects in the prior art and provide microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules, preparation methods and applications. They can utilize the bacterial microenvironment (such as enzymes) to trigger the release of active ingredients cinnamaldehyde and gallium ions, and synergistically achieve efficient removal of planktonic bacteria and biofilms by cinnamaldehyde and gallium ions. They can be used to prepare food preservatives, antibacterial agents or antibacterial drugs.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules includes the following steps: Step 1, metal coordination crosslinking: Gallium salt solution is added dropwise to tannic acid-cinnamaldehyde emulsion. After the addition is completed, the mixture is cured. Gallium ions coordinate with tannic acid to form a metal-polyphenol network core loaded with cinnamaldehyde, and a core dispersion is obtained. Step 2, Hyaluronic Acid Coating: The core dispersion obtained in Step 1 is added to the hyaluronic acid solution to coat the surface of the metal-polyphenol network core with hyaluronic acid. Then, the core is centrifuged and washed to obtain microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules.
[0008] As a further technical solution, the preparation of tannic acid-cinnamaldehyde emulsion includes: adding tannic acid to an aqueous solvent, adjusting the pH to 6.5-7.5, then adding cinnamaldehyde, and ultrasonically emulsifying under ice-water bath conditions to obtain tannic acid-cinnamaldehyde emulsion.
[0009] As a further technical solution, the ultrasonic power is 200 W, with a working time of 3 seconds, an interval of 3 seconds, and a processing time of 5 minutes; As a further technical solution, in step 1, the concentration of tannic acid in the tannic acid-cinnamaldehyde emulsion is 1-5 mg / mL, and the concentration of cinnamaldehyde is 2-20 mg / mL. As a further technical solution, in step 1, the concentration of the gallium salt aqueous solution is 2-10 mg / mL; As a further technical solution, in step 1, the molar ratio of tannic acid to gallium ions is 1:1-3; As a further technical solution, in step 1, the dropping rate of the gallium salt aqueous solution is controlled to be completed in 10-30 minutes; the aging treatment time is 1-4 hours.
[0010] As a further technical solution, in step 2, the concentration of the hyaluronic acid solution is 1-5 mg / mL; As a further technical solution, in step 2, the washing liquid used for washing is deionized water; As a further technical solution, in step 2, the centrifugation speed is 10,000 rpm and the centrifugation time is 10 min.
[0011] As a further technical solution, in step 2, the molecular weight of the hyaluronic acid is 100 kDa-200 kDa.
[0012] Microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules prepared by the aforementioned preparation method.
[0013] The aforementioned microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules have a core-shell structure. The core layer is a self-assembled metal-polyphenol network core loaded with cinnamaldehyde, and the shell layer is a hyaluronic acid layer covering the core layer. The nanocapsules prepared in this invention have a core-shell structure. The core is an emulsion droplet formed by polyphenol ligands and cinnamaldehyde, cross-linked at the interface through metal ions. The outer shell is a camouflage layer formed by hyaluronic acid or its salts / derivatives, resulting in enzyme-triggered metal-polyphenol / cinnamaldehyde nanocapsules disguised by hyaluronic acid.
[0014] The application of the aforementioned microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules in the preparation of food preservatives, antibacterial agents, or antimicrobial drugs.
[0015] As a further technical solution, the antibacterial agent is a bacterial and / or bacterial biofilm antibacterial agent; the antibacterial drug is a bacterial and / or bacterial biofilm antibacterial drug.
[0016] As a further technical solution, the antibacterial drug includes a topical drug, which includes medical antibacterial dressings, medical disinfectant preparations, etc.
[0017] As a further technical solution, the bacteria are selected from one or more of Staphylococcus aureus, Listeria monocytogenes, and Escherichia coli; As a further technical solution, the antibacterial agent or antimicrobial drug can inhibit bacterial growth, prevent bacterial biofilm formation, and remove existing bacterial biofilms.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules prepared in this invention utilize the characteristic of pathogenic bacteria (such as Staphylococcus aureus) secreting hyaluronidase. The HA shell is specifically degraded under the action of enzymes, exposing the core and triggering the rapid release of cinnamaldehyde and gallium ions. In an enzyme-free and sterile environment, the HA shell remains intact, effectively preventing the volatilization and oxidation of cinnamaldehyde and reducing non-specific consumption.
[0019] 2. The microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules prepared in this invention release gallium ions as a "Trojan horse" to competitively replace bacterial iron metabolism and disrupt the respiratory chain; cinnamaldehyde can destroy the integrity of bacterial cell membranes, leading to leakage of contents; the synergistic effect of the two significantly reduces the risk of bacteria developing drug resistance.
[0020] 3. The microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules provided by the present invention have HA shells that give the nanocapsules good hydrophilicity and bioadhesion, which helps them to attach to the surface of biofilms; the active ingredients released after enzymatic hydrolysis can effectively penetrate the dense extracellular polymer matrix and remove deep bacteria in the membrane.
[0021] 4. The microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules prepared by this invention are prepared entirely in aqueous phase with no organic solvent residue; all raw materials are food-grade or biocompatible materials, which meet food safety requirements. Attached Figure Description
[0022] Figure 1 These are actual images of the HA@Ga-TA / CIN nanocapsules of this invention and HA@TA / CIN nanocapsules without gallium ions after centrifugation; exist Figure 1 In the image, a: HA@Ga-TA / CIN nanocapsules; b: HA@TA / CIN nanocapsules without gallium ions.
[0023] Figure 2 This is an optical microscope image of the HA@Ga-TA / CIN nanocapsules of this invention.
[0024] Figure 3 This is a particle size distribution (DLS) diagram of the HA@Ga-TA / CIN nanocapsules of the present invention.
[0025] Figure 4 This is a comparison diagram of the zeta potentials of the HA@Ga-TA / CIN nanocapsules of the present invention and Ga-TA / CIN nanocapsules without HA shells.
[0026] Figure 5 The minimum inhibitory concentration (MIC) of the HA@Ga-TA / CIN nanocapsules and the Ga-TA / CIN nanocapsules without HA shells of the present invention against Staphylococcus aureus is OD. 600 picture.
[0027] Figure 6 The graph shows the antibacterial activity test results of HA@Ga-TA / CIN nanocapsules of different concentrations and Ga-TA / CIN nanocapsules without HA shells according to the present invention. exist Figure 6 In the image, a: Colony diagram on LB agar plate; b: Total colony count (Log).10 c: CFU / mL bar chart; c: bacterial survival rate chart; Figure 7 This is a comparison chart showing the performance of different concentrations of HA@Ga-TA / CIN nanocapsules and Ga-TA / CIN nanocapsules without HA shells in inhibiting biofilm formation. exist Figure 7 In the image, a: Crystal violet staining; b: Inhibition rate of biofilm formation. Figure 8 This is a comparison chart showing the performance of HA@Ga-TA / CIN nanocapsules of different concentrations and Ga-TA / CIN nanocapsules without HA shells in destroying mature biofilms. exist Figure 8 In the image, a: Crystal violet staining; b: Destruction rate of mature biofilm. Detailed Implementation
[0028] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0030] Unless otherwise specified, the test reagents and consumables used in the following examples are all conventional biochemical reagents and can be obtained commercially.
[0031] Unless otherwise specified, all experimental methods described are conventional methods.
[0032] To better understand the present invention, the following description, in conjunction with the accompanying drawings and embodiments, will further illustrate the present invention, but the implementation of the present invention is not limited thereto.
[0033] Example 1 A method for preparing microbial infection-responsive metal-polyphenol / cinnamaldehyde (HA@Ga-TA / CIN) nanocapsules includes the following steps: Step 1, Solution preparation: Preparation of 2 mg / mL tannic acid solution: Weigh 20 mg of tannic acid (TA), dissolve it in 10 mL of deionized water, and carefully adjust the pH to 7.0 using 0.1 M NaOH solution to obtain a tannic acid solution with a concentration of 2 mg / mL; Preparation of HA solution: Weigh 20 mg of sodium hyaluronate (molecular weight 100 kDa-200 kDa), dissolve it in 10 mL of deionized water, and prepare a 2 mg / mL sodium hyaluronate solution. Ga 3+ Solution preparation: Weigh 50 mg of gallium nitrate (Ga(NO3)3), dissolve it in 5 mL of deionized water, and prepare a 10 mg / mL Ga solution. 3+ Solution for later use; Step 2, Preparation of tannic acid-cinnamaldehyde emulsion: Take 5 mL of tannic acid solution with a concentration of 2 mg / mL, add 100 μL (about 105 mg) of cinnamaldehyde (purity > 98%), and then perform ultrasonic emulsification under ice-water bath conditions. Set the ultrasonic power to 200 W, work for 3 s and then pause for 3 s, and perform ultrasonic emulsification for a total of 5 min to obtain a milky white tannic acid-cinnamaldehyde emulsion. At this time, cinnamaldehyde is wrapped by tannic acid molecules to form tiny oil droplets, constructing the preliminary emulsion core structure. Step 3: Metal coordination crosslinking forms a metal-polyphenol network core: While stirring at 500 rpm, 1000 μL of Ga was added dropwise to the tannic acid-cinnamaldehyde emulsion obtained in step 2. 3+ Solution, with Ga 3+ The addition of the solution slightly increases the viscosity of the reaction system and may cause a slight change in the color of the Ga-TA coordination color (slightly pale yellow), indicating that gallium ions coordinate with tannic acid. After the addition is complete, continue stirring for 1 h to allow the metal-polyphenol network core structure to be fully formed and stabilized, and obtain Ga-TA / CIN nanocore dispersion. Step 4: Hyaluronic Acid Shell Coating: While stirring at 500 rpm, slowly pour 5 mL of sodium hyaluronate solution into the Ga-TA / CIN nanocore dispersion obtained in Step 3. Maintain stirring for 15-30 min, allowing HA molecules to aggregate and coat the Ga-TA / CIN core surface through non-covalent interactions (electrostatic adsorption and hydrogen bonding), forming a hyaluronic acid camouflage shell. During stirring, the reaction system will slightly become turbid or the viscosity will slightly increase, indicating that HA has successfully adsorbed onto the core surface. After the reaction is complete, centrifuge the reaction solution at 10,000 rpm for 10 min, and carefully aspirate the supernatant (to remove uncoated cinnamaldehyde and free HA / Ga-TA / CIN). 3+ The precipitate was washed three times with deionized water and then resuspended in 5 mL of PBS buffer or deionized water to obtain the HA@Ga-TA / CIN nanocapsule dispersion, which was stored at 4°C in the dark.
[0034] Example 2 A method for preparing microbial infection-responsive metal-polyphenol / cinnamaldehyde (HA@Ga-TA / CIN) nanocapsules includes the following steps: Step 1, Solution preparation: Preparation of 2 mg / mL tannic acid solution: Weigh 40 mg of tannic acid (TA), dissolve it in 10 mL of deionized water, and carefully adjust the pH to 7.0 using 0.1 M NaOH solution to obtain a tannic acid solution with a concentration of 4 mg / mL; Preparation of HA solution: Weigh 30 mg of sodium hyaluronate (molecular weight 100 k kDa-200 kDa), dissolve it in 10 mL of deionized water, and prepare a 3 mg / mL sodium hyaluronate solution. Ga 3+ Solution preparation: Weigh 40 mg of gallium nitrate (Ga(NO3)3), dissolve it in 5 mL of deionized water, and prepare an 8 mg / mL Ga solution. 3+ Solution for later use; Step 2, Preparation of tannic acid-cinnamaldehyde emulsion: Take 2.5 mL of tannic acid solution with a concentration of 4 mg / mL, add 100 μL (about 105 mg) of cinnamaldehyde (purity > 98%), and then perform ultrasonic emulsification under ice-water bath conditions. Set the ultrasonic power to 200 W, work for 3 s and then pause for 3 s, and perform ultrasonic emulsification for a total of 5 min to obtain a milky white tannic acid-cinnamaldehyde emulsion. At this time, cinnamaldehyde is wrapped by tannic acid molecules to form tiny oil droplets, constructing the preliminary emulsion core structure. Step 3: Metal coordination crosslinking forms a metal-polyphenol network core: While stirring at 500 rpm, 1200 μL of Ga was added dropwise to the tannic acid-cinnamaldehyde emulsion obtained in step 2. 3+ Solution, with Ga 3+ The addition of the solution slightly increases the viscosity of the reaction system and may cause a slight change in the color of the Ga-TA coordination color (slightly pale yellow), indicating that gallium ions coordinate with tannic acid. After the addition is complete, continue stirring for 1 h to allow the metal-polyphenol network core structure to be fully formed and stabilized, and obtain Ga-TA / CIN nanocore dispersion. Step 4: Hyaluronic Acid Shell Coating: While stirring at 500 rpm, slowly pour 5 mL of sodium hyaluronate solution into the Ga-TA / CIN nanocore dispersion obtained in Step 3. Maintain stirring for 15-30 min, allowing HA molecules to aggregate and coat the Ga-TA / CIN core surface through non-covalent interactions (electrostatic adsorption and hydrogen bonding), forming a hyaluronic acid camouflage shell. During stirring, the reaction system will slightly become turbid or the viscosity will slightly increase, indicating that HA has successfully adsorbed onto the core surface. After the reaction is complete, centrifuge the reaction solution at 10,000 rpm for 10 min, and carefully aspirate the supernatant (to remove uncoated cinnamaldehyde and free HA / Ga-TA / CIN). 3+ The precipitate was washed three times with deionized water and then resuspended in 5 mL of PBS buffer or deionized water to obtain the HA@Ga-TA / CIN nanocapsule dispersion, which was stored at 4°C in the dark.
[0035] Comparative Example 1: HA@TA / CIN without gallium ions The preparation method of gallium-ion-free HA@TA / CIN includes the following steps: Step 1, Solution preparation: Preparation of 2 mg / mL tannic acid solution: Same as in Example 1; Preparation of HA solution: Same as in Example 1; Step 2, Preparation of tannic acid-cinnamaldehyde emulsion: Same as in Example 1; Step 3, Hyaluronic acid shell coating: While stirring at 500 rpm, slowly pour 5 mL of sodium hyaluronate solution into the tannic acid-cinnamaldehyde emulsion obtained in Step 3, and keep stirring for 15-30 min to obtain gallium-free HA@TA / CIN.
[0036] The HA@TA / CIN dispersion prepared in Comparative Example 1 and the HA@Ga-TA / CIN dispersion prepared in Example 1 were centrifuged under the same conditions (10,000 rpm, 10 min) and their appearances were compared. The results are shown in the figure. Figure 1 .
[0037] like Figure 1 As shown: 1) In Comparative Example 1, an oily liquid appeared at the bottom of the centrifuge tube after centrifugation of HA@TA / CIN, while the supernatant was almost transparent. This indicates that the emulsion structure formed by tannic acid emulsification is extremely unstable under conditions lacking gallium ion coordination crosslinking. During centrifugation, a large amount of emulsion broke down, and cinnamaldehyde precipitated from the core and accumulated at the bottom of the tube, exhibiting obvious oil-water separation. This shows that HA@TA / CIN failed to form a stable nanocapsule structure, and the encapsulation rate of cinnamaldehyde was extremely low (see...). Figure 1 a).
[0038] 2) A large amount of uniform and dense milky white precipitate was visible at the bottom of the HA@Ga-TA / CIN centrifuge tube in Example 1. The amount of precipitate was significantly greater than that in Comparative Example 1, and the supernatant was relatively clear. This indicates that under the coordination and cross-linking effect of gallium ions, the metal-polyphenol network core structure was stably formed, and cinnamaldehyde was effectively encapsulated in the nanocapsule core. After centrifugation, it could settle in the form of intact particles, the encapsulation rate was significantly improved, and the nanocapsule structure had good stability.
[0039] The above comparison results intuitively show that Ga 3+ -TA coordination crosslinking is a key step in constructing a stable metal-polyphenol network core and achieving efficient loading of cinnamaldehyde.
[0040] Comparative Example 2: Ga-TA / CIN without HA shell A method for preparing a Ga-TA / CIN nanoparticle dispersion without an HA shell includes the following steps: Similar to Example 1, the difference is that after completing step (3), the HA coating in step (4) is no longer performed. Instead, the obtained Ga-TA / CIN core dispersion is directly transferred into a centrifuge tube, centrifuged at 10,000 rpm for 10 min, the supernatant is discarded, and the precipitate is resuspended in deionized water. The washing is repeated 3 times. Finally, the obtained precipitate is resuspended in 5 mL of PBS buffer or deionized water to obtain a Ga-TA / CIN nanoparticle dispersion without HA shell.
[0041] This comparative example was used to compare the HA@Ga-TA / CIN nanocapsules obtained in Example 1 to evaluate the effect of the HA shell on the material's surface potential, enzyme-responsive release behavior, and antibacterial properties.
[0042] Example of effect 1: The HA@Ga-TA / CIN nanocapsules obtained in Example 1 were characterized by optical microscopy and subjected to dynamic light scattering (DLS) and zeta potential measurements. The results are shown in [Figure 1]. Figure 2-4 ; (1) Characterization by optical microscopy: from Figure 2 The optical microscopy characterization results show that the HA@Ga-TA / CIN nanocapsules have a spherical or near-spherical structure, the particles are uniformly dispersed, and there is no obvious aggregation.
[0043] (2) Dynamic light scattering (DLS) and Zeta potential: like Figure 3 and Figure 4As shown, the hydrated particle size of the HA@Ga-TA / CIN nanocapsules is approximately 1243 nm, and the polydispersity index (PDI) is <0.2, indicating good dispersibility. In Comparative Example 2, the zeta potential of the uncoated Ga-TA / CIN core is approximately -21.2 mV, while in Example 1, the zeta potential of the nanocapsules coated with HA decreases to approximately -27.2 mV, confirming the successful coating of HA.
[0044] Example 2: Hyaluronidase Response and Release Performance Experiment To verify the responsive release characteristics of the nanocapsules of this invention to hyaluronidase, the HA@Ga-TA / CIN nanocapsules prepared in Example 1 were dispersed in PBS buffer (pH 7.4), with and without hyaluronidase groups, and incubated with shaking at 37°C. Samples were taken at preset time points, and after centrifugation to separate the supernatant, the release of cinnamaldehyde was determined by ultraviolet spectrophotometry, and the release of gallium ions was determined by ICP-OES. The cumulative release rate was calculated, and the results are shown in Table 1. Table 1 The results showed that in the system without hyaluronidase, the release rates of cinnamaldehyde and gallium ions from the HA@Ga-TA / CIN nanocapsules were low, with a cumulative release rate of 24.3% for cinnamaldehyde and 19.1% for gallium ions after 3 hours. This indicates that the hyaluronic acid shell can effectively inhibit the non-specific leakage of active components under non-triggered conditions. However, in the system containing hyaluronidase, the hyaluronic acid shell degraded, and the release rates of cinnamaldehyde and gallium ions increased. The cumulative release rate of cinnamaldehyde increased to 68.4% and the cumulative release rate of gallium ions increased to 53.6% after 3 hours. These results demonstrate that the nanocapsules of this invention exhibit clear hyaluronidase responsiveness and can achieve targeted release of active components in the environment of pathogenic bacteria-related enzymes.
[0045] The Ga-TA / CIN nanoparticles without HA coating obtained in Comparative Example 2 were used as a control. The results showed that there was no significant difference in the release of Ga-TA / CIN between the enzyme-containing and enzyme-free groups, while the release of HA@Ga-TA / CIN increased in the enzyme-containing group, further proving that the enzyme response characteristics originated from the hyaluronic acid shell rather than the natural disintegration and release of the core itself.
[0046] Example of effect 3: Antibacterial properties 1. Using Staphylococcus aureus (ATCC 26003) as an indicator bacterium, the antibacterial activity of HA@Ga-TA / CIN obtained in Example 1 and Ga-TA / CIN obtained in Comparative Example 2 was evaluated.
[0047] The bacterial culture was diluted to 5 × 10⁻⁵ using the micro-broth dilution method. 5 CFU / mL, different concentrations of material were added, and after incubation at 37℃ for 12 h, 200 μL of bacterial suspension was taken to measure its optical density. The results are shown below. Figure 5 .
[0048] like Figure 5 As shown, the OD values of the bacterial solutions after treatment increased with increasing material concentration in both groups of samples. 600 The values of both decreased significantly, indicating that both can effectively inhibit the growth and reproduction of Staphylococcus aureus. Based on OD... 600 The results showed that the minimum inhibitory concentration (MIC) of HA@Ga-TA / CIN and Ga-TA / CIN against Staphylococcus aureus was 25 μg / mL, indicating that the HA shell coating did not weaken the antibacterial activity of the core material.
[0049] 2. Take 100 μL of bacterial suspension treated with different concentrations of materials and disperse it evenly on LB agar plates. Incubate at 37℃ for 24 h. Count bacterial colonies using the plate count method and calculate the sterilization rate. The results are shown in [Figure number missing]. Figure 6 .
[0050] from Figure 6 As can be seen from a, compared with the blank control group, the number of colonies on the plates was significantly reduced after treatment with HA@Ga-TA / CIN or Ga-TA / CIN, and the number of colonies continued to decrease with increasing treatment concentration, showing a clear concentration dependence. Figure 6 b and Figure 6 Quantitative results showed that at 25 μg / mL, the number of viable bacteria in both groups decreased significantly, and the bacterial survival rate was significantly reduced. At a concentration of 25 μg / mL, both groups achieved a sterilization rate of over 99.9%, which is the minimum bactericidal concentration (MBC) of the sample. These results indicate that the nanocapsules of this invention not only possess good antibacterial activity but also have strong direct bactericidal ability.
[0051] Experimental Example 4: Anti-biofilm performance Staphylococcus aureus readily forms dense biofilms, which is a core reason for bacterial resistance, recurrent infections, and failure of antimicrobial treatment. This invention evaluates the antibiofilm properties of HA@Ga-TA / CIN and Ga-TA / CIN materials from two dimensions: inhibition of biofilm formation and destruction of mature biofilms.
[0052] (1) Experiment on inhibition of biofilm formation: Staphylococcus aureus bacterial solution (10) 6CFU / mL was added to 96-well plates, along with different concentrations of HA@Ga-TA / CIN and Ga-TA / CIN (0, 25, 50, 100, 200 μg / mL). The plates were incubated at 37℃ for 24 h to allow bacteria to attempt biofilm formation in the presence of nanocapsules. After incubation, the culture medium was discarded, and the plates were washed three times with PBS to remove airborne bacteria. The plates were then stained with 0.1% crystal violet solution for 30 min, washed with PBS, dissolved in 30% glacial acetic acid, and the absorbance was measured at 572 nm. The inhibition rate of biofilm formation was calculated, and the results are shown below. Figure 7 .
[0053] like Figure 7 As shown, both materials exhibited significant concentration-dependent inhibitory effects on Staphylococcus aureus biofilm formation. In the blank control group (0 μg / mL), a large number of thick, dense biofilm structures formed at the bottom of the wells, staining a deep purple with crystal violet, indicating that Staphylococcus aureus could adhere, aggregate, and stably form a biofilm. For the HA@Ga-TA / CIN nanocapsule system, the biofilm inhibition rate was approximately 28.0% in the 25 μg / mL treatment group; the inhibition rate increased to approximately 73.7% in the 50 μg / mL group; the inhibition rate further increased to approximately 91.3% in the 100 μg / mL group; and almost no visible biofilm residue was observed in the 200 μg / mL treatment group, with crystal violet staining nearly blank, indicating a biofilm inhibition rate of approximately 100%, demonstrating that this concentration completely prevented Staphylococcus aureus biofilm formation. Compared to HA@Ga-TA / CIN nanocapsules, the biofilm inhibition effect of Ga-TA / CIN nanocores was weaker at the same concentration, with a particularly significant difference in biofilm formation inhibition efficiency at low and medium concentration gradients. The reason is that the exposed Ga-TA / CIN core lacks a hydrophilic adhesive shell of hyaluronic acid, has poor water dispersibility and bacterial interface enrichment ability, and lacks enzyme-responsive targeted drug release characteristics. In the culture system, the active components are easily consumed non-specifically by environmental organic matter, and cannot continuously and efficiently intervene in the bacterial adhesion and aggregation process. On the other hand, HA@Ga-TA / CIN relies on the excellent hydrophilicity and bioadhesion of the hyaluronic acid shell, which can effectively accumulate on the bacterial surface and precisely trigger the release of active components in the bacterial microenvironment, thereby greatly improving the early inhibition effect of biofilm.
[0054] (2) Experiment on the destruction of mature biofilms: Staphylococcus aureus bacterial solution (10) 6(CFU / mL) was added to 96-well plates and incubated at 37℃ for 24 h to allow mature biofilm formation. After discarding the culture medium, the plates were gently washed once with PBS, and different concentrations of HA@Ga-TA / CIN and Ga-TA / CIN (0, 25, 50, 100, 200 μg / mL) were added, followed by incubation at 37℃ for another 12 h. After incubation, the solution was discarded, the plates were washed three times with PBS, and crystal violet staining and quantification were performed as described above. The biofilm destruction rate was calculated, and the results are shown in [Figure number missing]. Figure 8 .
[0055] like Figure 8 a and Figure 8 As shown in b, the biofilm destruction results are consistent with the biofilm inhibition experiment. Both HA@Ga-TA / CIN and Ga-TA / CIN can remove existing mature biofilms, and the destruction effect is also concentration-dependent, but overall lower than that in the biofilm formation inhibition experiment. This indicates that the dense structure of mature biofilms has a certain hindering effect on material penetration. For the HA@Ga-TA / CIN group, the destruction rates of mature biofilms at 25, 50, 100, and 200 μg / mL were approximately 12.7%, 36.7%, 69.1%, and 90.3%, respectively. Compared with the Ga-TA / CIN group, HA@Ga-TA / CIN has a higher destruction rate of mature biofilms at the same concentration (the corresponding values for the Ga-TA / CIN group were 6.66%, 28.9%, 55.5%, and 82.4%, respectively), indicating that the HA shell coating is beneficial to improving the material's ability to penetrate and remove mature biofilms.
[0056] In summary, HA@Ga-TA / CIN nanocapsules not only significantly inhibit the formation of Staphylococcus aureus biofilm, but also effectively destroy existing mature biofilms. Compared with Ga-TA / CIN without a HA shell, HA@Ga-TA / CIN exhibits superior anti-biofilm properties, indicating that the HA shell plays a positive role in the material's anti-biofilm performance.
[0057] The embodiments described above are merely preferred embodiments of the present invention, and not an exhaustive list of all possible implementations of the present invention. Any obvious modifications made by those skilled in the art without departing from the principles and spirit of the present invention should be considered to be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules, characterized in that, Includes the following steps: Step 1, metal coordination crosslinking: Gallium salt solution is added dropwise to tannic acid-cinnamaldehyde emulsion. After the addition is completed, the mixture is cured. Gallium ions coordinate with tannic acid to form a metal-polyphenol network core loaded with cinnamaldehyde, and a core dispersion is obtained. Step 2, Hyaluronic Acid Coating: The core dispersion obtained in Step 1 is added to the hyaluronic acid solution to coat the surface of the metal-polyphenol network core with hyaluronic acid. Then, the core is centrifuged and washed to obtain microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules.
2. The method for preparing a microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsule as described in claim 1, characterized in that, The preparation of tannic acid-cinnamaldehyde emulsion includes: adding tannic acid to an aqueous solvent, adjusting the pH to 6.5-7.5, then adding cinnamaldehyde, and ultrasonically emulsifying under ice-water bath conditions to obtain tannic acid-cinnamaldehyde emulsion.
3. The method for preparing a microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsule as described in claim 1, characterized in that, In step 1, the concentration of tannic acid in the tannic acid-cinnamaldehyde emulsion is 1-5 mg / mL, and the concentration of cinnamaldehyde is 2-20 mg / mL. The concentration of the gallium salt aqueous solution is 2-10 mg / mL; The molar ratio of tannic acid to gallium ions is 1:1-3; In step 1, the dropping rate of the gallium salt aqueous solution is controlled to be completed in 10-30 minutes; the aging treatment time is 1-4 hours.
4. The method for preparing a microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsule as described in claim 1, characterized in that, In step 2, the concentration of the hyaluronic acid solution is 1-5 mg / mL; In step 2, the washing solution used for washing is deionized water; The centrifugation speed was 10,000 rpm, and the centrifugation time was 10 min; The molecular weight of the hyaluronic acid is 100 kDa-200 kDa.
5. Microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules prepared by the preparation method according to any one of claims 1-4.
6. The microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsule as described in claim 5, characterized in that, It has a core-shell structure, with a core layer consisting of a self-assembled metal-polyphenol network core loaded with cinnamaldehyde, and a shell layer consisting of a hyaluronic acid layer covering the core layer.
7. The application of the microbial infection-responsive metal-polyphenol / cinnamaldehyde nanocapsules as described in claim 6 in the preparation of food preservatives, antibacterial agents, or antimicrobial drugs.
8. The application as described in claim 7, characterized in that, The antibacterial agent is a bacterial and / or bacterial biofilm antibacterial agent; the antibacterial drug is a bacterial and / or bacterial biofilm antibacterial drug.
9. The application as described in claim 8, characterized in that, The bacteria are selected from one or more of Staphylococcus aureus, Listeria monocytogenes, and Escherichia coli.
10. The application as described in claim 7, characterized in that, The antibacterial agent or antimicrobial drug can inhibit bacterial growth, prevent bacterial biofilm formation, and remove existing bacterial biofilms.